POTENSI TUMBUHAN OBAT DI AREA KAMPUS II UIN ALAUDDIN SAMATA GOWA - -, Bauq Farhatul Wahidah (Teknosains, 2013)
The research aims to examine to potencial medicinal plants thatâs grow in the area of uin alauddin campus 2, samata gowa. The crusing method used at eight observation stations. Furthermore, medicinal plantswere identified and descriptively analyzed. The result showsthat in the campus areathere are 43 species of medicinal plants identified, which are mostly wild plantsKey words: Medicinal plants, UIN Alauddin